BL_GERICHTE 470 19 149 vom 27. August 2019 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Strafrecht, vom 27. August 2019 (470 19 149) - BL Gerichte (2019)
Erkennungsdienstliche Erfassung/DNA-Probenahme/Erstellung DNA-Profil